Pelatihan Pengelolaan Media Sosial Sebagai Upaya Promosi Produk UMKM Desa Balongdowo: Social Media Management Training as an Effort to Promote MSME Products in Balongdowo Village - Pristalisa, Mendi Endritha; Febriana, Poppy; Rochmaniah, Ainur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
This community engagement discusses understanding in making online sales stalls through Instagram media for the two MSME actors. By going through activities in social media management training as an effort to promote the MSME products Salted Egg Pak Poh and Mama Bagas's Roasted Rice in Balongdowo village, as well as introducing the importance of managing social media that can be owned with the aim of building Brand Awareness. By going through the stages namely observation, training, lectures, practice for carrying out the training, and ending with an evaluation of the results of the activities that have been carried out. Then the results obtained by the two owners of MSME Salted Egg Pak Poh and Mama Bagas's Roasted Rice have mastered the strategy for using sales stalls through Instagram media and mastering strategies in using social media to build Brand Awareness in the long term.